2016
DOI: 10.1039/c6an02145j
|View full text |Cite
|
Sign up to set email alerts
|

Antibody purification via affinity membrane chromatography method utilizing nucleotide binding site targeting with a small molecule

Abstract: Here, we present an affinity membrane chromatography technique for purification of monoclonal and polyclonal antibodies from cell culture media of hybridomas and ascites fluids. The m-NBST method utilizes the nucleotide-binding site (NBS) that is located on the Fab variable domain of immunoglobulins to enable capturing of antibody molecules on a membrane affinity column via a small molecule, tryptamine, which has a moderate binding affinity to the NBS. Regenerated cellulose membrane was selected as a matrix du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…In Figure 3, there was an absence of additional bands in the SDS-PAGE and immunoblot, which verified the purity of the IgG from the rabbit of non-purified anti-sera. These results were according to the previous studies, in which the pure IgG was obtained from polyclonal antibodies through affinity chromatography (Kang et al, 2016;Sadeghi et al, 2018, Mustafaoglu et al, 2016.…”
Section: Sds-page and Western Blot Of Purified Poly-iggssupporting
confidence: 89%
See 1 more Smart Citation
“…In Figure 3, there was an absence of additional bands in the SDS-PAGE and immunoblot, which verified the purity of the IgG from the rabbit of non-purified anti-sera. These results were according to the previous studies, in which the pure IgG was obtained from polyclonal antibodies through affinity chromatography (Kang et al, 2016;Sadeghi et al, 2018, Mustafaoglu et al, 2016.…”
Section: Sds-page and Western Blot Of Purified Poly-iggssupporting
confidence: 89%
“…However, the purification technique may and may not enhance the binding affinity of the antibody. As reported by Mustafaoglu et al (2016), purification of antibodies did not improve the binding activity of the antibody due to the antibody activity (including both antigen detection and Fc recognition) was utterly preserved after purification. Limited studies were reported on the difference of binding affinity of purified poly-IgG or non-purified anti-sera in immunoassay.…”
Section: Introductionmentioning
confidence: 85%
“…A predominantly convective transport mechanism of the solutes through the membrane pores to the adsorption sites is superior to the intraparticle diffusion transport mechanism of resinbased chromatography. Until now, various types of membranes have been investigated for protein purication, 1,2 i.e., membrane chromatography based on ion exchange, [3][4][5][6] affinity, [7][8][9] and hydrophobic interactions. 10,11 Stimuli-responsive membrane can change structural and functional properties (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Sericin, a silkworm polypeptide, upon blending with chitosan membranes with a ratio of 4:1, was capable of recognizing serum albumin and led to a 45% increase in adsorption capacity compared to chitosan alone [ 65 ]. For antibody purification, an alternative for affinity ligands is tryptamine, which can bind the nucleotide-binding site on the Fab domain of the antibodies [ 66 ]. This strategy created both monoclonal and polyclonal antibodies purified from cell culture media of ascites fluids.…”
Section: Development Of Stationary Phases For Selective Protein Captu...mentioning
confidence: 99%